Analisis Implementasi Akuntansi Murabahah pada BMT Iqtisaduna Yogyakarta Berdasarkan Fatwa DSN MUI - Huzeini Alghifari; Ery Nugroho; Ibnu Kamal; Falikhatun Falikhatun (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2022)
This research is a qualitative descriptive study that aims to analyze the implementation of murabahah accounting at BMT Iqtisaduna Yogyakarta. Data collection is done by using the methods of observation, documentation, and interviews. The analysis technique of this research uses a qualitative comparative analysis technique, namely by comparing the Fatwa of DSN MUI No. 111/DSN-MUI/IX/2017 with the results of observations at BMT Iqtisaduna Yogyakarta. The results of this study indicate that the provisions of the murabahah contract applied by BMT Iqtisaduna Yogyakarta are in accordance with DSN MUI.